PORE PRESSURE ESTIMATION AND ITS THREEDIMENSIONAL DISTRIBUTION IN PIN FIELD, JAMBI SUB BASIN, SOUTH SUMATRA BASIN - Rifulton, Afiff
The Pin Field is one of the oil and gas fields situated in the Jambi Sub-Basin, South Sumatra Basin. This field has been developed since 2016. Regional studies indicate the presence of overpressured zones within this field; however, the understanding of pore pressure characteristics and its three-dimensional (3D) distribution remains limited. This study aims to estimate the pore pressure of Gumai dan Talang Akar Formations using Eaton’s method and generate its 3D distribution using pressure measurement and wireline logs data from 19 wells, as well as 3D seismic velocity. Pore pressure characterization reveals two pressure regimes in this field: low overpressure in the Upper Talang Akar Formation (UTAF) and hydrostatic in the Gumai and Lower Talang Akar (LTAF) Formations. The pore pressure of the overpressured zones ranges up to 2486 psi. Analyses of pressure-stress profiles with depth and wireline log data indicate loading as the overpressure-generating mechanism. The 3D distribution of pore pressure shows that the top of the overpressure zone is between 3414 and 4347 ft, shallowing towards the northwest and following the stratigraphy, which is also shallowing due to the basement high. The 3D pore pressure distribution model in this study is essential, particularly for designing exploration drilling in the Pin Field, as pore pressure is one of the factors determining the drilling success and efficiency.